2023
DOI: 10.3389/fmicb.2023.1096022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vaccines on clinical characteristics of convalescent adult patients infected with SARS-CoV-2 Omicron variant: A retrospective study

Abstract: IntroductionThe protective effect of SARS-CoV-2 vaccines has become a global focus due to Omicron variant pandemic. The effects of various SARS-CoV-2 vaccines are diverse. However, studies on the effect of domestic vaccines on clinical characteristics in convalescent adult patients infected with the Omicron variant are lacking.MethodsIn this retrospective, single-center cohort study, the effect of three domestic vaccines on clinical characteristics of convalescent adult patients infected with the Omicron varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Specifically, the most widely administered SARS-CoV-2 vaccine is the inactivated one in mainland China 35 . Although domestic vaccines may not provide complete protection against Omicron variants, they do offer significant safeguards for adult patients 36 . Wang J et al found that vaccinated adult patients had notably lower levels of Interleukin-6 and C-reactive protein compared to unvaccinated patients, revealing that the domestic vaccines provide significant protection against inflammation reduction in adult patients during the recovery phase 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the most widely administered SARS-CoV-2 vaccine is the inactivated one in mainland China 35 . Although domestic vaccines may not provide complete protection against Omicron variants, they do offer significant safeguards for adult patients 36 . Wang J et al found that vaccinated adult patients had notably lower levels of Interleukin-6 and C-reactive protein compared to unvaccinated patients, revealing that the domestic vaccines provide significant protection against inflammation reduction in adult patients during the recovery phase 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Although domestic vaccines may not provide complete protection against Omicron variants, they do offer significant safeguards for adult patients 36 . Wang J et al found that vaccinated adult patients had notably lower levels of Interleukin-6 and C-reactive protein compared to unvaccinated patients, revealing that the domestic vaccines provide significant protection against inflammation reduction in adult patients during the recovery phase 36 . In our study, over 90% of the patients had been vaccinated, which likely contributed to a notable reduction in the rate of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation